The Role Of The Board Of Directors In The Financial Performance Of Companies An Empirical Study On Banks Listed On The Damascus Securities Exchange - جديد غيث (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the relationship between the formation a board of directors and financial performance of companies. Especially the banks operating in the Damascus Stock Exchange, and for that, the researcher collected data on the independent variable represented in formation a board of directors from the governance reports published on the website of the Syrian Securities and Financial Markets Authority, as well as data on the dependent variable represented in financial performance through special financial statements and reports for banks listed on the Damascus Securities Exchange and the Syrian Securities and Markets Authority. The 14 listed banks in the Damascus Securities Exchange and the Syrian Securities and Markets Authority, during the period from 2011 to 2016, the data was studied through the Eviews10 program. The study reached a set of results, the most important of which are: There is a negative relationship between the variables of independence of the board of directors and dual role to president of the board of directors with the rate of return on assets, and this relationship is not statistically significant, and there is a positive relationship between the variables of the size of the board of directors and the number of board meetings annually with the rate of return on assets, but it is not statistically significant.